Language Disorders Therapy Mobile Application for Preschoolers - SOH, YING YING; MOHD YUSOF, MUNIRAH (Applied Information Technology And Computer Science, 2024)
The Language Disorders Therapy Mobile application is an application that focuses on preschoolers between the ages of 3 to 5 who have language disorders at Elite Speech Therapy. However, some language disorders in the language development stage of preschoolers will seriously affect their academic performance, social interaction, and emotional health. Therefore, this study aims to design, develop, and test the functionality of a Language Disorders Therapy Mobile Application. In addition, the mobile application was developed using an agile methodology approach and an object-oriented approach. The Java programming language is used on the Android Studio software to develop the application and NoSQL as a database. This application can improve the language skills, social skills, and quality of life of the preschoolers, and the language therapists provide personalized intervention plans targeting each preschooler’s needs and weaknesses to achieve effectiveness. In addition, it is expected to help deal with problems early in development, minimizing possible effects and providing a better opportunity for preschoolers to develop standard language skills and enhance social skills. Overall, the application will serve as a bridge for collaboration between therapists and parents, helping them focus on preschooler’s language development.